Parkinson's disease severity and motor subtype influence physical capacity components - Marcelo Pinto Pereira; Paulo Henrique Silva Pelicioni; Lilian Teresa Bucken Gobbi (Universidade Estadual Paulista (UNESP), 2013)
The severity of Parkinson's disease (PD) and PD's motor subtypes influence the components of physical capacity. The aim of this study was to investigate the impact of both PD severity and motor subtype in the performance of these components. Thirty-six PD patients were assigned into four groups: Tremor (TD) initial and TD mild, akinetic-rigid (AR) initial, and AR mild. Patients' strength, balance, coordination, mobility and aerobic capacity were evaluated and groups were compared using a two-way ANOVA (severity and subtype as factors). AR presents a poorer performance than TD in almost all tests. Also this performance was worsened with the advance of the disease in AR, contrary to TD. We conclude that AR and TD subgroups are different about their performance on physical capacity components, moreover, this performance worsens with the advance of the disease of the AR group, but not for TD.